Бабушка сказала сидеть тихо - Реньжина Настасья (Steklo, 2024)
Экземпляры: ф.18 (20250319) / Инвентарный номер: 5210 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 39 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44